Sistema de Alimentación para una Antena de Haz de Seguimiento - Castañeda Fandiño, José Ignacio; Susca Díaz, Cristian (Ingeniería, 2004)
The feeding system, analyzed in this paper, shows how a certain phase angle in a signal of high frequency can be obtained by modulation of signals. It consists in two stages, the first one is about a phase modulation system in low frequency where the angular movement is obtained relatively easy. This signal in low frequency is translate to another signal in high frequency with a balanced modulator and a filter which eliminates the lower side band. Finally, the obtained phase angle is into the properties of linearity.